The Inner Conflict of the Main Character in the Novel “Tatkala Leukemia Meretas Cinta” by Siti Fadilah Supari - Alhafidz, Zidan Rizka (Lia Center of Research and Education, 2025)
This study examines the personality structure and defense mechanisms of the main character in the novel Tatkala Leukemia Meretas Cinta using Sigmund Freud’s psychoanalytic theory. The novel was chosen because it vividly portrays psychological conflicts experienced by the main character when faced with a profoundly painful reality. The research employed a qualitative descriptive method with a content analysis approach. The data consist of narrative and dialogue excerpts that reflect the psychological aspects of the main character. Data collection was conducted through library research by reading and analyzing the novel in depth. The findings were then interpreted using Freud’s concepts of the id, ego, and superego, as well as defense mechanism theory. The results show that the main character’s personality structure consists of the id, dominated by emotional impulses such as anxiety, fear, and the need for self-preservation; the ego, which mediates rational decision-making; and the superego, which guides moral and spiritual values. The character employs six defense mechanisms repression, sublimation, rationalization, displacement, reaction formation, and regression to cope with psychological distress arising from life’s hardships. This study contributes to a deeper understanding of psychological representation in Indonesian literature and serves as a reference for future studies exploring the intersection between literature and psychology, particularly in examining how individuals confront trauma through psychological defense mechanisms.